Highly efficient green synthesized cerium oxide nanoparticles from Tectona grandis seed extract for Rhodamine B dye degradation and biological applications - Akhilesh T. Shetty; Divya N. Shetty; Narasimha Raghavendra; Suman Rani (Next Materials)
This study presents a sustainable process for creating cerium oxide nanoparticles utilizing an extract from the Tectona grandis seed, which act as stabilizing and reducing agents. XRD, SEM, FT-IR and UV-Vis spectroscopy are used to thoroughly assess the successful creation of nanoparticles. Studies are conducted on CeO2 and doped CeO2 nanoparticles for Rhodamine B dye degradation, antioxidants, and antibacterial. In FT-IR, CeO2 NPs had a stretching frequency of 540 cm−1 and doped CeO2 NPs of 580 cm−1. Crystalline nature of CeO2 NPs and doped CeO2 NPs was confirmed by the XRD results. For both CeO2 NPs and doped CeO2 NPs, the maximum degradation of Rhodamine B is seen at 60 min. The ideal pH is found to be 4.0 for CeO2 NPs and 9.0 for doped CeO2 NPs after studies at various pH values of 4, 7, and 9. For deterioration seen at 30 min, the maximum concentration effect was 20 ppm for both doped CeO2 NPs and CeO2 NPs. Theoretical study by Monte Carlo (MC) simulation and Sorption isotherm model confirms the Rhodamine B dye degradation in the presence of cerium oxide nanoparticles in the aqueous system. The antibacterial activity of two microorganisms, S. aureus and E. coli, was then investigated. The E. Coli bacteria displayed the zone of inhibition for CeO2 NPs at 10 mm and for doped CeO2 NPs at 12 mm. The zone of inhibition for doped CeO2 NPs was observed by S. aureus bacteria at 15 mm, while the zone of inhibition for CeO2 NPs was observed at 14 mm. Therefore, the lower zone of inhibition in bacteria is seen for CeO2 NPs. The maximal levels of their antioxidant for CeO2 NPs and doped CeO2 NPs are 94 % and 84 %, respectively.